Desarrollo e implementación de un sistema de gestión odontológica orientado a la web, utilizando el FRAMEWORK DJANGO para la clínica Obandental ubicado en el cantón Machala” - Loor Campoverde, Hipólito Alexander (2015)
In research conducted at the Clinic Obandental city of Machala, it was evident the disadvantages and problems arising when carrying out their dental management; because it did not have a computer system that allows them to organize and automate their management processes. Therefore, was the need to develop and implement a Management System Odontológica oriented web, using the Django Framework, it is written in the Python programming language and is based on a Model Architecture - View Controller; development methodology also UWE software, which is a method of engineering WEB based UML oriented objects, which can be used for applications WEB specification was employed. the Framework of Twitter called Bootstrap, which lets you create web interfaces with CSS and Javascript in a dynamic manner was used to build interfaces; as manager database system Postgresql was used, which allows working with a large number of users and data; the use of AJAX was also used, to thereby make changes on pages without having to recharge, improving interactivity, speed the system. All the tools that were used in the development and implementation of web system are free software, which reduced costs. Through the integrated web system is able to manage all the processes involved in dental management Obandental Clinic, such as booking appointments, patient registration, registration of medical record with their respective odontogram, control inventory dental materials and control of the charges made by the different treatments provided by the Clinic. Therefore, the automated web system any manual record was exposed to loss or deterioration; providing security and integrity information, thereby expediting the dental management.